Analyzing the Influence of Intellectual Capital, Human Capital, AI Integration, and Tax Incentives on Company Growth - Bilqis Tarwiyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This qualitative research aims to investigate the intricate interplay between intellectual capital, human capital, AI integration, and tax incentives concerning company growth. Employing a holistic approach, the study conceptualizes a comprehensive model to understand the dynamic relationships among these variables. Through purposive sampling, data are gathered from a diverse range of companies across industries. Utilizing thematic analysis, the data is systematically scrutinized to unveil patterns and insights. Preliminary findings suggest that intellectual capital and human capital serve as crucial drivers, augmented by the strategic integration of AI and favorable tax incentives. The study contributes to a nuanced understanding of the factors influencing company growth in the contemporary business landscape.